Aspirin enhances the clinical efficacy of anti-tuberculosis therapy in pulmonary tuberculosis in patients with type 2 diabetes mellitus. Issue 10 (2nd October 2020) - Wang, Wenjie; Du, Zhixiang; Ni, Mingyue; Wang, Zijian; Liang, Manman; Sheng, Haoyu; Zhang, Aiping; Yang, Jianghua
Abstract: Background: Tuberculosis in patients with diabetes mellitus is characterised by rapid disease progression, poor treatment efficacy, poor prognosis and poses a new challenge in tuberculosis treatment and control. Methods: Patients with pulmonary TB and type 2 DM were recruited at Yijishan Hospital of Wannan Medical College. A total of 348 patients were randomly assigned to two groups. The aspirin group (aspirin + TB/DM) included 174 patients who received anti-TB therapy and enteric-coated aspirin tablets (100 mg/tablet). The control group (placebo + TB/DM) included 174 patients who received anti-TB therapy and enteric-coated placebo tablets (an identical tablet containing no drug). Eighty-two patients in the aspirin group and 86 in the control group completed the trial and were included in the analysis. Clinical characteristics, laboratory test results, imaging data and side effects of aspirin were monitored. Results: Aspirin treatment affect certain signs and symptoms. The erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) levels were lower in the aspirin group than in the control group after treatment (Both p  = .000). The sputum-negative conversion rate was 86.7% in the aspirin group, significantly higher than in the control group (53.8%) ( p  = .031). After two months of treatment, the differences in the number of cases with cavities, the number of cavities, and maximum diameter of cavities in the aspirin group were statistically significant ( p  = .003, p  = .023 and p  = .015 respectively). Conclusion: Our findings suggest that aspirin may improve treatment in patients with pulmonary TB and type 2 DM.